Importance of anatomical leaf-blade features for the characterization of medicinal Commelinaceae in the Rio de la Plata area (Argentina) - Novoa, María Cecilia (2016)
In this paper we examine the leaf-blade anatomy of: Commelina erecta L. var. erecta f. erecta, Tradescantia fluminensis Vell., Tripogandra diuretica (Mart.) Handlos, and T. glandulosa (Seub.) Rohweder. These species grow in the coastal region of the Río de la Plata (Argentina) where they are used as ophthalmic, diuretic, antirheumatic, sudorific, and digestive. The aim of this study was to establish diagnostic features in order to deepen knowledge of these medicinal species and thus, get a valuable tool to establish their botanical identity. The leaves were prepared according to usual methods for light and scanning electron microscopes. Histochemical techniques to identify starch, lipophilic substances, mucilage, tannins, and oxalate salts were performed. The ions analysis of oxalate salts using a scanning electron microscope equipped with an energy dispersive spectrometer was performed. The main differential traits found were: stomata hexaperiginous in C. erecta var. erecta f. erecta, and tetraperigenous in T. fluminensis and Tripogandra species; leaf blade margins with parenchyma in C. erecta var. erecta f. erecta and T. fluminensis, and with fibers in Tripogandra species; presence of druses in palisade parenchyma of the blade in T. fluminensis, and the hairy index.